Peningkatan Pengetahuan Pola Makan Sehat melalui Flash Card - Zubaedah Zubaedah; Dwi Puji Lestari (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2017)
The purpose of this research was to determinate the proccess of implementation flasch card to increase knowledge of healty dietary habit in Group B Al Hub Kebayoran Baru South of Jakarta. This research is an action research which refers to the model of a classroom Action Research Kemmis and Mc. Taggart. The subject of this research are children in Group B Al Hub Kebayoran Baru South of Jakarta there are 10 children. The steps of this research : (1) Planing (2) Action (3) Observation (4) Reflection. Data analysis used quantitative and qualitative. Data analysis qualitative used Miles and Hubberman model. This research do in two cycles, there are cycle I and II. The end result of the overall analysis of the data is the percentage in 91,17% cycles II which showed from precycle is 29,37 % up to cycles I 61,94%.